Olahraga Renang: Tinjauan Kritis tentang Kinerja, Biomekanika, Kesehatan, dan Risiko Cedera (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This article presents a structured literature review of scientific journal publications for the period 2021–2025 to examine the determinants of performance, health benefits, injury risk, and training implications on swimming. Data sources are obtained from various relevant online scientific databases, then selected based on predetermined criteria and synthesized thematically through critical reading of the latest empirical evidence. The results of the review show that swimming performance cannot be explained by general physical capacity alone, but is the result of an interaction between anthropometric characteristics, muscle strength, torso control, start and turn quality, and the ability to maintain propulsive phases efficiently. The literature also shows that ground strength training, core training, and inspirer muscle training provide a positive transfer to performance, especially in the sprint number and acceleration phases. On the other hand, the risk of injury is most consistently found in the shoulder and lower back, particularly when the volume of exercise increases without adequate load monitoring. Clinically and recreationally, exercise in the water also provides benefits to physical and psychological health, especially in adult and elderly populations. This review concludes that the development of an effective swimming training program needs to balance performance improvement, injury prevention, and the individual needs of swimmers. However, the results of this study are still limited to articles published during the period 2021–2025 and are influenced by the heterogeneity of the research design and the characteristics of the participants in each study analyzed.